Analysis of Teachers' Pedagogical Competence in Handling Children with Special Needs in Inclusive Schools (Case Study in Talenta Kindergarten & Fun and Play Kindergarten, Semarang City) - Firdaus Sa'adah; Naili Rohmah (Qalamuna)
The study aimed to analyse teachers' pedagogical competence in dealing with children with special needs in inclusive schools. This research is important because the government has established an inclusion system in all schools. Inclusive schools have students from different backgrounds. So that teacher competence becomes very important, especially pedagogical competence, because this is the key to successful learning, in qualitative research conducted through observation, interviews, and documentation. Seeing field conditions directly, looking at documentation of lesson plans to evaluations, and interviewing the teachers involved can provide more in-depth information: triangulating time, sources, and techniques tested data. The results explained that Fun and Play Kindergarten and Talenta Kindergarten teachers had the best pedagogical skills. This can be seen from the pedagogical competence of teachers according to Permendikbud Number 137 in assessing aspects of child development; evaluating theories of play and learning; creating development activities that are by the curriculum; organising educational development activities; and developing children's potential.